Infant Massage: Examining the Influence of Health Education on Maternal Attitudes and Practices - Namirah, Dela (HM Publisher, 2024)
Infant massage has been recognized for its potential benefits in promoting infant health and development, as well as enhancing maternal-infant bonding. However, the adoption of infant massage practices can be influenced by various factors, including maternal attitudes and knowledge. Health education interventions have been proposed as a means to improve maternal attitudes and practices related to infant massage. This study aimed to investigate the impact of a structured health education program on maternal attitudes and practices towards infant massage. A randomized controlled trial was conducted involving 120 mothers of infants aged 3-6 months. Participants were randomly assigned to either an intervention group (receiving a structured health education program on infant massage) or a control group (receiving routine care). Data on maternal attitudes and practices towards infant massage were collected at baseline and three months post-intervention using validated questionnaires. The intervention group demonstrated a significant improvement in maternal attitudes towards infant massage compared to the control group (p < 0.001). Additionally, the intervention group reported a higher frequency of infant massage practices and increased confidence in performing infant massage techniques. In conclusion, the findings suggest that a structured health education program can effectively enhance maternal attitudes and practices toward infant massage. The implementation of such programs in healthcare settings may contribute to increased adoption of infant massage, potentially leading to improved infant health and well-being.